2011
DOI: 10.1155/2011/138341
|View full text |Cite
|
Sign up to set email alerts
|

Herpes Simplex Virus Hepatitis in an Immunocompetent Adult: A Fatal Outcome due to Liver Failure

Abstract: Objective. To present a case of a healthy 41-year-old female who developed fulminant hepatic failure leading to death. The cause of hepatic failure identified on postmortem exam was herpes simplex virus hepatitis. Design. Observation of a single patient. Setting. Intensive care unit of a tertiary care university teaching hospital in Canada. Patient. 41-year-old previously healthy female presenting with a nonspecific viral illness and systemic inflammatory response syndrome. Intervention. The patient was treate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
26
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 23 publications
(52 reference statements)
0
26
0
Order By: Relevance
“…Hepatitis secondary to infection with HSV serotype 1 or 2 is a rare diagnosis that has a propensity to rapidly progress to fulminant liver failure [3], with mortality rates that approach 90% [4]. HSV hepatitis most commonly affects patients with impaired immunity and pregnant women in their third trimester, though literature reports have reported up to 25% of cases in immunocompetent individuals [3].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hepatitis secondary to infection with HSV serotype 1 or 2 is a rare diagnosis that has a propensity to rapidly progress to fulminant liver failure [3], with mortality rates that approach 90% [4]. HSV hepatitis most commonly affects patients with impaired immunity and pregnant women in their third trimester, though literature reports have reported up to 25% of cases in immunocompetent individuals [3].…”
Section: Discussionmentioning
confidence: 99%
“…Patients often present with nonspecific flu-like symptoms including fever, myalgias, and abdominal pain [6,7]. e characteristic mucocutaneous herpetic skin lesions are found only in 30-50% of cases [4]. Common laboratory findings included leukopenia, thrombocytopenia, and coagulopathy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Norvell et al's literature review showed that a clinical suspicion of HSV hepatitis was raised in only 22.6% of 137 cases. Laboratory investigations often demonstrate leukopenia, thrombocytopenia, coagulopathy, a relatively low bilirubin level, and a significant increase in liver enzymes (100‐ to 1000‐fold), with AST greater than ALT . In our case, the diagnosis was mistaken for an acute cholecystitis, because of the confirmed calculous gallbladder and major gallbladder wall edema, which are common findings in cystic fibrosis patients.…”
Section: Discussionmentioning
confidence: 67%
“…That said, IFN responsiveness of the circulating immune cells clearly contributes to controlling generalized infections, particularly in the liver. The incidence of HSV-induced liver failure is well established in the case report literature, with most cases occurring in immunocompromised patients, although some immunocompetent patients succumb to the disease (21,42,43). Although this disease has gained attention, especially in the transplant literature, to our knowledge there has been no basic research on HSV hepatotropism and the role of innate immunity therein.…”
Section: Discussionmentioning
confidence: 99%